Oxocomplexes of U(vi) with 8-hydroxyquinoline-5-sulfonate in solution: structural studies and photophysical behaviour. Issue 29 (26th May 2017) - Ramos, M. Luísa; Justino, Licínia L. G.; Barata, Rui; Costa, Telma; Nogueira, Bernardo A.; Fausto, Rui; Burrows, Hugh D.
Abstract : The dioxouranium species UO2 2+ forms a nonluminescent 1 : 2 complex with 8-HQS having a distorted pentagonal bipyramidal geometry. Abstract : Multinuclear ( 1 H and 13 C) NMR, and Raman spectroscopy, combined with DFT calculations, provide detailed information on the complexation between U(vi ) oxoions and 8-hydroxyquinoline-5-sulfonate (8-HQS) in aqueous solution. Over the concentration region studied, U(vi ) oxoions (uranyl ions) form one dominant complex with 8-HQS in water in the pH range 3–6, a mononuclear 1 : 2 (metal : ligand) complex, with the metal centre (UO2 2+ ) coordinated to two 8-HQS ligands, together with one or more water molecules. An additional minor 1 : 1 complex has also been detected for solutions with a 1 : 1 metal : ligand molar ratio. The geometry of the dominant complex is proposed based on the combination of the NMR and Raman results with DFT calculations. Further information on the electronic structure of the complex has been obtained from UV/visible absorption and luminescence spectra. The complex of U(vi ) and 8-HQS is non-luminescent, in contrast to what has been observed with this ligand and many other metal ions. We suggest that this is due to the presence of low-lying ligand-to-metal charge transfer (LMCT) states below the emitting ligand-based and uranyl-based levels which quench their emission. These studies have fundamental importance and are also relevant in the context of environmental studies, and the water soluble ligand 8-HQS has been chosen for application in uranium remediation of aqueous environments.